A questão da contemporaneidade nas artes : Heidegger e a poiesis - Silva, Felipe Escopelli Moulim da (2018)
This thesis broaches questions of the essence of art comprehended in Martin Heidegger’s thought as poiesis, concerning the issue of the truth understood as aletheia – the openness of being. This project aims at accentuating the relationship between the to